2012
DOI: 10.1176/appi.ps.201100446
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Mentoring Program for PTSD Clinic Managers in the U.S. Department of Veterans Affairs

Abstract: Mentees who were actively engaged with the mentoring program reported significant benefits. Efforts are under way to enhance the program by strengthening mentor selection and training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…When ISPs are providing consultation/facilitation , five common components emerged across studies: (1) identifying the support needs of those involved in the consultation/facilitation efforts, for example, through formalized, periodic needs assessments (Duffy et al, 2012), structured interviews (Bice-Urbach & Kratochwill, 2016), or by explicitly inviting stakeholders to articulate their support needs in each session (Akin, 2016; Chilenski et al, 2016); (2) educating and professionally supporting these stakeholders, for example, through processes such as learning from others (Akin, 2016), role-plays (Barac et al, 2018), didactic teaching (Beidas et al, 2013; Chaffin et al, 2016), answering questions (Chilenski et al, 2016; Hurtubise et al, 2016; Kelly et al, 2000), or offering advice (Rosen et al, 2012); (3) monitoring the progress and/or performance of stakeholders, for example, by measuring fidelity (Bice-Urbach & Kratochwill, 2016; Caron & Dozier, 2019; Eiraldi et al, 2018; Murray et al, 2018), program outcomes (Funderburk et al, 2015; Olson et al, 2018), or progress toward other implementation or service goals (Chilenski et al, 2016; Holtrop et al, 2008; Preast & Burns, 2018); (4) identifying implementation barriers and problems faced as part of the change efforts, typically related to learning a new practice (Dusenbury et al, 2010; Eiraldi et al, 2018; Kauth et al, 2010; Nadeem, Gleacher, Pimentel, et al, 2013) and/or enabling its implementation within a particular local context (Rosella et al, 2018; Saldana & Chamberlain, 2012; Tierney et al, 2014); and (5) identifying potential solutions to these problems, including next steps to initiate these. This final step was at times characterized as “troubleshooting” (Chaffin et al, 2016; Hodge et al, 2017; Meropol et al, 2014) signaling a more urgent and ad hoc type of character that this strategy could take.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When ISPs are providing consultation/facilitation , five common components emerged across studies: (1) identifying the support needs of those involved in the consultation/facilitation efforts, for example, through formalized, periodic needs assessments (Duffy et al, 2012), structured interviews (Bice-Urbach & Kratochwill, 2016), or by explicitly inviting stakeholders to articulate their support needs in each session (Akin, 2016; Chilenski et al, 2016); (2) educating and professionally supporting these stakeholders, for example, through processes such as learning from others (Akin, 2016), role-plays (Barac et al, 2018), didactic teaching (Beidas et al, 2013; Chaffin et al, 2016), answering questions (Chilenski et al, 2016; Hurtubise et al, 2016; Kelly et al, 2000), or offering advice (Rosen et al, 2012); (3) monitoring the progress and/or performance of stakeholders, for example, by measuring fidelity (Bice-Urbach & Kratochwill, 2016; Caron & Dozier, 2019; Eiraldi et al, 2018; Murray et al, 2018), program outcomes (Funderburk et al, 2015; Olson et al, 2018), or progress toward other implementation or service goals (Chilenski et al, 2016; Holtrop et al, 2008; Preast & Burns, 2018); (4) identifying implementation barriers and problems faced as part of the change efforts, typically related to learning a new practice (Dusenbury et al, 2010; Eiraldi et al, 2018; Kauth et al, 2010; Nadeem, Gleacher, Pimentel, et al, 2013) and/or enabling its implementation within a particular local context (Rosella et al, 2018; Saldana & Chamberlain, 2012; Tierney et al, 2014); and (5) identifying potential solutions to these problems, including next steps to initiate these. This final step was at times characterized as “troubleshooting” (Chaffin et al, 2016; Hodge et al, 2017; Meropol et al, 2014) signaling a more urgent and ad hoc type of character that this strategy could take.…”
Section: Resultsmentioning
confidence: 99%
“…Studies reflected that consultation/facilitation was provided to individuals (Bradshaw et al, 2012; Rosen et al, 2012) as well as groups of stakeholders (Kousgaard & Thorsen, 2012; Murray et al, 2018) and occurred either in-person (Anyon et al, 2016; Dobbins et al, 2018; Eiraldi et al, 2018), or remotely (C. H. Brown et al, 2014; Gustafson et al, 2013; Kauth et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported that for stakeholders experiencing this trust and sense of safety, it became easier to share details about their own clinical or educational practice (Bidassie et al, 2015), and to buy into and experiment with new approaches to this practice (Akin, 2016;Anyon et al, 2016;Duffy et al, 2012). This became possible because stakeholders felt that they were not being judged or evaluated negatively (Shernoff et al, 2015) and therefore could give up a part of their control (Hurlburt et al, 2014), both in their relationship to ISPs and in their relationships with other stakeholders also involved in the implementation support (Beidas et al, 2013;Gustafson et al, 2013;Rosen et al, 2012;Rushovich et al, 2015). Both of these types of relationships were described as requiring a sense of safety for stakeholders to share experience and engage in joint learning and hence highlighted as points of attention for ISPs' work.…”
Section: Stakeholder Responses To Ispsmentioning
confidence: 99%
“…For some studies, ISP support structures were formalized even further by being integrated into the ISP intervention. This occurred, for example, by establishing two-layered implementation support structures consisting of, for example, an external facilitator, taking the outside support role otherwise assigned to, for example, principal investigators, and an internal facilitator providing implementation support within organizations or systems they themselves were part of (McCullough et al, 2017;Rosen et al, 2012). Another study described the use of knowledge brokers together with an additional "broker to the brokers" (Rivard et al, 2010(Rivard et al, , p. 1583.…”
Section: Contextual Influences On the Work Of Ispsmentioning
confidence: 99%
See 1 more Smart Citation